2022
DOI: 10.3390/jof8050547
|View full text |Cite
|
Sign up to set email alerts
|

Peel Diffusion and Antifungal Efficacy of Different Fungicides in Pear Fruit: Structure-Diffusion-Activity Relationships

Abstract: Fungal pathogens can invade not only the fruit peel but also the outer part of the fruit mesocarp, limiting the efficacy of fungicides. In this study, the relationships between fungicide structure, diffusion capacity and in vivo efficacy were evaluated for the first time. The diffusion capacity from pear peel to mesocarp of 11 antifungal compounds, including p-aminobenzoic acid, carbendazim, difenoconazole, dipicolinic acid, flusilazole, gentamicin, kojic acid, prochloraz, quinolinic acid, thiophanate methyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…Considering that DPA‐caused effects were only detected for a few days, DPA must show preventive efficacy only when the pathogen attacks the fruits just after DPA treatment, but it may not protect the fruits for long periods. Previous reports indicated that DPA shows relatively high stability in plant tissues, with approximately 50% degradation in pear skin after 5 days 36 and no obvious degradation in pear trunk after 20 days 23 …”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Considering that DPA‐caused effects were only detected for a few days, DPA must show preventive efficacy only when the pathogen attacks the fruits just after DPA treatment, but it may not protect the fruits for long periods. Previous reports indicated that DPA shows relatively high stability in plant tissues, with approximately 50% degradation in pear skin after 5 days 36 and no obvious degradation in pear trunk after 20 days 23 …”
Section: Discussionmentioning
confidence: 98%
“…36 Fungicides typically show low diffusion capacities and remain in the fruit skin, allowing the advancement of the pathogens throughout fruit internal phases. 36 This could explain why strong antifungal compounds, such as prochloraz and thiram, showed weak antifungal activities against B. cinerea in kiwifruit. The higher efficacy of DPA in kiwifruit compared to in vitro can be explained by the strong defense response triggered by DPA in kiwifruit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations